Changes in speed and agility of young football players under the experimental training programme - Stankovic, M.; Bojic, I.; Mihajlovic, M. (23rd International Scientific Conference "FIS COMMUNICATION 2021", 2021)
The aim of the research was to determine to what extent motor abilities, speed and agility, in young football players (aged 7 to 10) would change after a six-week long programmed training process. Thirty football players aged 7 to 10 from football club Vucje in Vucje (Serbia) participated in the research. They had been training football for at least one year. The following measuring instruments were applied for estimating speed and acceleration: 5m Sprint, 10m Sprint and 40m Sprint. A different set of measuring instruments was applied for estimating agility: 505 agility test, Balsom run and Arrowhead agility drill. The subjects were tested before and after the training programme which took place during the preparation period in 45-minute sessions in the first part of the training, two times a week. The results show that there is a statistically significant difference between the first two speed tests (5m - .000; 10m - .001), whereas the third test shows no such statistically significant difference (40m - .118). There is no statistically significant difference in the first agility test between two testing situations (505 agility test - .116) but there is a significant difference in the remaining two agility tests (Arrowhe"pd agility drill - .000; Balsom agility test - .001). Student's t-test results show that the applied 6-week long training process had a positive effect on the changes in the starting speed (5m Sprint) and acceleration (10m Sprint) results. However, there was no improvement in the maximum speed results (40m Sprint). The applied training programme positively affected agility in two out of three applied measuring instruments (Arrowhead agility drill and Balsom agility test).